Sustaining peace through psychologically informed policies : the geohistorical context of Malaysia - Christie, Daniel J.; Noor, Noraini M. (Springer, 2012)
In this chapter we explore some ways in which psychological principles can inform national policies designed to prevent intergroup violence and promote intergroup harmony. We begin by briefly positioning the discipline of psychology within the larger context of scholarship in Peace and Conflict Studies (PCS), a transdisciplinary field where multiple levels of analysis are examined, including the policy level. We discuss the degree to which psychology, as the science of thoughts, feelings, and behavior has made inroads into the study of PCS. We suggest one barrier to fully integrating psychological principles into PCS is the lack of scholarship in psychology that works across levels, from micro (individual) through meso (group and intergroup) and macro (societal) levels. Then we turn to a particular geohistorical context, Malaysia, and describe how macro-level policies have been advanced at the national level to improve relations between ethnic groups. We conclude with some principles of psychological science that could be used more effectively to inform policies designed to prevent ethnic conflict and promote social justice in the Malaysian context.